STUDY OF THE EFFECT OF OBESITY ON IMMUNE CELLS ACTIVITY AND CARDIOVASCULAR DISEASE RISK IN EL-OUED (ALGERIA) WOMEN - ACHCHI, IKRAM; DEROUICHE, SAMIR (Innovare Journal of Medical Sciences, 2021)
Objective: This study was conducted to find out the effect of obesity on immune cells activity and some biochemical markers in women. Methods: The experimentation is carried out on 30 voluntary individuals were divided into two groups; 15 women with obesity (Body Mass Index [BMI]>30) were selected, On the other hand, we took 15 witnesses (BMI<30). All the volunteers were subjected to estimate the lipid profile, biochemical, and hematological parameters. Results: Results obtained show that there was a significant increase of blood glucose (p<0.05), triglyceride (p<0.05) and uric acid (p<0.001) and no significant change of other biochemical markers in obese people’s group when compared to the control subjects. In addition, the hematological results demonstrated that there was a significant decrease (p<0.05) of lymphocytes, hemoglobin, hematocrit, and mean corpuscular volume levels (p<0.01) in women with obesity compared to the controls. Conclusion: Our study reveals that the obesity may be induce the sever alteration in lipid profile which cause the cardiovascular risk for this population. In addition, the obesity causes a remarkable change in some biochemical markers and blood constituent’s anemia or other metabolic disorder in the body.